Kepentingan Ekonomi Indonesia Dalam Ekspor Karet Alam Ke Jepang Pada Masa Tahun 2017 - Hastuti, Dyah Ayu Widya; Martin, Ali (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2023)
For Indonesia, Japan is one of the largest trading partner countries in terms of Indonesian import exports. Japan is a country with economic growth that can be taken into account with other developed countries. Japan is an industrial country but the limitations of natural resources are one of natural rubber. This study aims to find out the purpose of Indonesia to export natural rubber to Japan in 2017. The theory used by the author is the theory of national interest. This research method uses qualitative methods. The results in the study explained that a cooperation between Indonesia and Japan has affected national economic interests. Indonesia's natural rubber exports to Japan have boosted the economy for Indonesia. The need for Japanese natural rubber is increasing due to Japan's industry as one of the largest automotive manufacturers in the world. There are economic ties between Indonesia and Japan from the past.